Cognitive Disorders In Acquired Sensorineural Hearing Loss, At The Ent Department Of The “Village Bondeko” Center, In Kinshasa - Masamba GR; Sokolo Gedikondele J; Longo-Mbenza B; Nganga Nkanga MS; Matanda Nzanza R; Matonda-ma-Nzuzi T; Ikanga J; Nge Okwe A; Lema Mabwaka G; Mawalala Malengele H; Nangi Mampuya C; Lumbu Malundama D (Neuropsychiatric Disease and Treatment)
Grace Réjane Masamba,1,2 Jerôme Sokolo Gedikondele,1 Benjamin Longo-Mbenza,3– 5 Mireille Solange Nganga Nkanga,6 Richard Matanda Nzanza,1,2 Thierry Matonda-ma-Nzuzi,7 Jean Ikanga,8 Augustin Nge Okwe,3 Gabriel Lema Mabwaka,1 Héritier Mawalala Malengele,3,9 Cédrick Nangi Mampuya,1 Damien Lumbu Malundama1 1Department of Specialties, Otolaryngology Department, University Clinics of Kinshasa, Faculty of Medicine, University of Kinshasa, Kinshasa, Democratic Republic of Congo; 2Faculty of Medicine, Protestant University of Congo, Kinshasa, Democratic Republic of Congo; 3Department of Public Health, Lomo University of Research, Kinshasa, Democratic Republic of Congo; 4Cardiology Service, Cliniques Universitaires de Kinshasa, Kinshasa, Democratic Republic of Congo; 5Walter Sisulu University, Mthatha, South Africa; 6Department of medical biology, clinical biology service, University of Kinshasa, Kinshasa, Democratic Republic of Congo; 7Department of psychiatry, Child psychiatry service, University of Kinshasa, Kinshasa, Democratic Republic of Congo; 8Department of psychiatry, Neuropsychology service, University of Kinshasa, Kinshasa, Democratic Republic of Congo; 9Department of Radiology and Medical Imaging, Kinshasa University Clinics, Université de Kinshasa, Kinshasa, Democratic Republic of CongoCorrespondence: Benjamin Longo-Mbenza, Faculty of Health Science, Mthatha, South Africa, Tel +243 814396257, Email longombenza@gmail.comContext: Several data from the literature have focused on the relationship between congenital sensorineural hearing loss, as well as acquired hearing loss, and their impact on cognition and the risk of dementia. However, few studies have been conducted on this subject in countries where access to hearing rehabilitation measures is limited. Thus, the objective of the present study was to investigate the relationship between sensorineural hearing loss and cognitive disorders in a correlational approach.Methods: This is a cross-sectional and analytical study conducted in the ENT department of the Center for the Disabled (visual, auditory, and mental) “Village Bondeko”, from June to September 2023, involving 150 adults (≥ 20 years) with acquired sensorineural hearing loss; without a history of neuropsychic disorders. Sensorineural hearing loss was confirmed by tonal threshold audiometry and characterized according to WHO criteria; cognitive disorders were defined according to the MoCA scale.Results: In total, 150 adults, including 78 men and 72 women, were collected in the present study. The average age was 54.11 ± 20 years, with extremes ranging from 20 to 87 years. In univariate analysis, there was a significant association (p< 0.0001) between the degree of hearing loss and cognitive disorders. The analysis of variance (ANOVA) comparing the means demonstrated a very significant correlation (p ˂ 0.0001) between the decline in cognitive functions and the severity of hearing impairment. The low level of education, marital status, and cardiovascular risk factors were associated with cognitive disorders; however, no association was demonstrated between advancing age, gender, socioeconomic status, and cognitive disorders in the study population.Conclusion: The present study has demonstrated the existence of an association between sensorineural hearing loss and cognitive disorders, involving a multidisciplinary and early management of sensorineural hearing loss.Keywords: sensorineural hearing loss, cognition, Kinshasa, Village Bondeko